(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the intricate artistry of poetry, focusing on the stylistic elements of rhythm, metre, and sound effects. It provides a thorough exploration of these components, elucidating their significance in shaping the texture, musicality, and emotional depth of poetic expression. The article begins by elucidating the concept of rhythm, portraying it as the heartbeat of poetry, setting the pace and musical cadence. It then progresses to discuss metre, delving into various poetic forms and meters such as iambic pentameter, trochaic octameter, and diverse metrical patterns prevalent in renowned poems. Further, the article explores the realm of sound effects in poetry, highlighting the use of literary devices such as alliteration, assonance, consonance, and onomatopoeia. Each device is exemplified through excerpts from classic poems, showcasing their role in enhancing auditory experiences and creating vivid imagery within the reader’s mind.